The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3390/pharmaceutics12111108
|View full text |Cite
|
Sign up to set email alerts
|

Mesoporous Materials for Drug Delivery and Theranostics

Abstract: Mesoporous materials, especially those made of silica or silicon, are capturing great interest in the field of nanomedicine [...]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 8 publications
(8 reference statements)
0
9
0
Order By: Relevance
“…This allows for exact checks on the release of cargo using a stimulus, whether internal and pathological characteristics are addressed or whether the physician is external. The regulation provided by the MSNs-responsive mechanism prevents the early release of the therapeutic substance, which could be important in preventing systemic toxicity (Cauda et al 2020;Zhou et al 2018;Vallet-Regí et al 2018). By modifying the physicochemical parameters of the chosen mesoporous materials, the nature of the drug's interactions can be altered.…”
Section: Applicability Of Mesoporous Materials For Sustained or Controlled Drug Delivery Systemsmentioning
confidence: 99%
“…This allows for exact checks on the release of cargo using a stimulus, whether internal and pathological characteristics are addressed or whether the physician is external. The regulation provided by the MSNs-responsive mechanism prevents the early release of the therapeutic substance, which could be important in preventing systemic toxicity (Cauda et al 2020;Zhou et al 2018;Vallet-Regí et al 2018). By modifying the physicochemical parameters of the chosen mesoporous materials, the nature of the drug's interactions can be altered.…”
Section: Applicability Of Mesoporous Materials For Sustained or Controlled Drug Delivery Systemsmentioning
confidence: 99%
“…Lately, scientists are making great efforts to improve the delivery and effectiveness of drugs using different approaches such as loading to polylactic acid microspheres, lipid nanoparticles or modifying them by glycosylation [ 36 , 37 , 38 , 39 , 40 ]. One of the possibilities for improving delivery and targeting is the use of mesoporous silica nanoparticles such as nontoxic SBA-15 (Santa Barbara Amorphous 15) [ 41 ]. Recently, it was reported that SBA-15 loaded with cisplatin, organotin (IV) compounds or titanocene dichloride and its derivatives can reduce tumor cell growth [ 42 , 43 , 44 , 45 , 46 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the apo inducing property of XN is transformed into a preference of autophagic cell death bling tumor repopulation in response to apoptotic-induced cell proliferation, a m nism that is tightly connected with therapy failure in advanced forms of cancer [47 Lately, scientists are making great efforts to improve the delivery and effectiveness of drugs using different approaches such as loading to polylactic acid microspheres, lipid nanoparticles or modifying them by glycosylation [36][37][38][39][40]. One of the possibilities for improving delivery and targeting is the use of mesoporous silica nanoparticles such as nontoxic SBA-15 (Santa Barbara Amorphous 15) [41]. Recently, it was reported that SBA-15 loaded with cisplatin, organotin (IV) compounds or titanocene dichloride and its derivatives can reduce tumor cell growth [42][43][44][45][46].…”
Section: Introductionmentioning
confidence: 99%
“…The crucial step in tracing bacteria is the selection of bacteriatracing agents, which include antibodies, [5] sugars, [6] antimicrobial peptides, [7] 67 Ga-citrate, radiolabeled leukocytes, and 18 F-fluorodeoxyglucose (FDG). [8][9][10] Ubiquicidin (UBI) [29][30][31][32][33][34][35][36][37][38][39][40][41] , which contains six positive amino acids, is a synthetic cationic bactericidal peptide fragment and can preferentially bind to the anionic bacterial cell membranes accumulated at the site of infection. [11] Based on this mechanism, UBI 29-41 combined with 99m Tc, 68 Ga, or near-infrared fluorescent dye has been widely investigated for use in the diagnosis of infection or as a target to trace bacteria.…”
Section: Introductionmentioning
confidence: 99%
“…[11] Based on this mechanism, UBI 29-41 combined with 99m Tc, 68 Ga, or near-infrared fluorescent dye has been widely investigated for use in the diagnosis of infection or as a target to trace bacteria. [12][13][14] Recently, 99m Tc-UBI [29][30][31][32][33][34][35][36][37][38][39][40][41] has been investigated as an adjunct to bone scans to differentiate between infected and aseptic loosening of prostheses before revision surgery. [15][16][17][18] Traditional antibiotics still have many shortcomings in the treatment of infection-related diseases.…”
Section: Introductionmentioning
confidence: 99%